MEMBANGUN LOYALITAS PELANGGAN PROVIDER INTERNET MELALUI PENINGKATAN DIMENSI PELAYANAN - Budi Harsono (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Explicitly, the company's goal is to make a profit. This will only be achieved, if you have customers. Therefore, building good relationships with customers is a necessity, one of which is by providing excellent service. In the internet service business, customer loyalty is a top priority. So, providing quality service is one of the best ways to maintain it. Indeed, this study seeks to examine and analyze the role of service on customer behavior of Internet service users in Indihome, South Jakarta. To study it, a quantitative approach was used with multiple regression analysis. The sampling technique used simple random, and data collection using a questionnaire. The number of respondents who are willing to be sampled is 100 people. The results of the study explained that loyalty occurs because customers are satisfied. In this study, customer satisfaction occurs because the services provided are very good, especially in terms of network reliability. Coupled with the friendliness and responsiveness of service providers, this reinforces positive perceptions of the company.